2015
DOI: 10.1039/c5cp03473f
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and transformation of fluorinated graphene induced by ultraviolet irradiation

Abstract: The effect of ultraviolet irradiation on fluorinated graphene (FG) dispersed in toluene was investigated for the first time. The chemical and physical characteristics of FG before and after ultraviolet irradiation were analyzed by UV-vis, FTIR, XPS,EDS, oxygen flask combustion (OFC), XRD, TGA, Raman, SEM, TEM and fluorescence spectroscopy. It is found that the F/C ratio initially decreases rapidly and then slowly with irradiation time, finally to 0.179 after irradiation for 48 h. The nature of partial C-F bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 49 publications
(71 reference statements)
1
22
0
Order By: Relevance
“…[[qv: 4a]],[[qv: 9a]] It was found that fluorinated graphene could be reduced by hydrazine, potassium iodide, ultraviolet irradiation and alkylamine compounds. [[qv: 9a]],[[qv: 12a]],61, 62 Robinson et al[[qv: 12a]] reported the low temperature chemical reduction of fluorographene by hydrazine with the process of 4CF n + n N 2 H 4 → 4C + 4 n HF + 2 n N 2 . Radek et al[[qv: 9a]] provided a pathway for defluorination using KI in DMF.…”
Section: Propertiesmentioning
confidence: 99%
“…[[qv: 4a]],[[qv: 9a]] It was found that fluorinated graphene could be reduced by hydrazine, potassium iodide, ultraviolet irradiation and alkylamine compounds. [[qv: 9a]],[[qv: 12a]],61, 62 Robinson et al[[qv: 12a]] reported the low temperature chemical reduction of fluorographene by hydrazine with the process of 4CF n + n N 2 H 4 → 4C + 4 n HF + 2 n N 2 . Radek et al[[qv: 9a]] provided a pathway for defluorination using KI in DMF.…”
Section: Propertiesmentioning
confidence: 99%
“…The reduction of s-FG was not feasible when methanol and water were used for the same aim. Beyond the above-mentioned approaches for the defluorination of FG, Ren et al reported that ultraviolet irradiation and aromatic solvents like toluene act synergistically for the partial defluorination of FG, controlled by the irradiation time [109] .…”
Section: Chemistrymentioning
confidence: 99%
“…Further, the concentration of F in FG/FGO can be decreased by the postsynthesis routes such as electron beam irradiation, hydrothermal, and ultrasonic treatments . Recently, it has shown that the CF bonds can be removed (defluorination) by exposing fluorinated graphene to ultraviolet irradiation for long time in aromatic solvents such as toluene and benzene . Further, another recent report explores the possibilities of defluorination by the solvent‐based treatment of fluorinated graphene, where the semiionic CF bonds were removed from fluorinated graphene upon its treatment with dipolar solvents such as N ‐methyl‐2‐pyrolidinone via ultrasonication …”
Section: Homo–lumo Gaps For Various Complexes 1 Au = 27 211 Evmentioning
confidence: 99%